Draft Annual Plan 1986-87 Volume II Part (A) Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1986)
Rural Works Department is primarily responsible for following works in Arunachal Pradesh. Minor irrigation, Soil & Water Conservation including Agricultural Machinery, Rural Water Supply (both MNP & ARP), Rural Road, Rural Housing, Renewable Source of Energy, NEC works, Buildings, CSS & Pilot Projects, Works of other sister departments like Agriculture, AH and Vety, General Administration and under DC's etc. etc.
Government of Arunachal Pradesh, Planning and Development Department